Organizational Behavior Analysis in the Context of Human Resource Management - Pratidhina, Puti Harissa; utami, Indri (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The company is faced with the challenge of managing employees with diverse needs and motivations in a dynamic business environment. This article reviews the factors that affect employee performance through the work environment, job satisfaction, and commitment to the organization. This study aims to analyze organizational behavior in the context of human resource management at Unilever Companies. The case study was conducted by conducting interviews with some employees and managers at Unilever Companies. The results of the study show that employees at Unilever Companies experience high levels of motivation, good job satisfaction, strong organizational commitment, and a collaborative work culture. These findings indicate that these factors play an important role in influencing organizational behavior in these companies. This study concludes that understanding and managing factors such as motivation, job satisfaction, organizational commitment, and collaborative work culture can have a positive impact on the performance and success of Unilever.